2009
DOI: 10.21608/mjae.2009.109761
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Studies on the Performance of Paddy and Rice Separator

Abstract: The performance of paddy and rice separator was theoretically and experimentally investigated as a function of change in separator sieve angle, paddy moisture content and feeding ratios. The separator performance was evaluated in terms of separator productivity, crack percentage, separator efficiency and energy requirements. The theoretical analyses reveal that the optimum sieve speed of 0.5 m/sec. (200 rpm) is recommended to prevent riding of material on the sieve surface. The experimental results reveal that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Motion of material over sieve surface : The motion of the grains over the sieve from the dehuller outlet to the end of the screen is important, as it helps in the uniform distribution of the grains over the screen. The motion of material over the sieve surface is calculated using the following equations (Fouda, 2011). ωgoodbreak=gμcosαsinαrcosα+μsinα where ω is the angular velocity (rad/s), g is the acceleration due to gravity (m/s), μ is the coefficient of friction, α is the angle of sieve from horizontal surface (degree), and r is the Length of crank shaft rod (m).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motion of material over sieve surface : The motion of the grains over the sieve from the dehuller outlet to the end of the screen is important, as it helps in the uniform distribution of the grains over the screen. The motion of material over the sieve surface is calculated using the following equations (Fouda, 2011). ωgoodbreak=gμcosαsinαrcosα+μsinα where ω is the angular velocity (rad/s), g is the acceleration due to gravity (m/s), μ is the coefficient of friction, α is the angle of sieve from horizontal surface (degree), and r is the Length of crank shaft rod (m).…”
Section: Methodsmentioning
confidence: 99%
“…Motion of material over sieve surface: The motion of the grains over the sieve from the dehuller outlet to the end of the screen is important, as it helps in the uniform distribution of the grains over the screen. The motion of material over the sieve surface is calculated using the following equations (Fouda, 2011).…”
Section: Slopementioning
confidence: 99%
“…After that, the brown rice and paddy rice on the shaking separator machine ran for a total of 150 s in all simulated cases. Fouda (2009) and Modi and Parkar (1979) applied Equation 6to find the effectiveness of the separation to be used as an index for separating the paddy rice from the brown rice. The separation effectiveness between brown rice and paddy rice was assigned a value from 0 to 1.…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…Kojima et al (1993) investigated the separation performance of rice movement and the distribution of brown rice and paddy rice on a shaking tray at various mixing ratios to determine the optimal operating conditions. In addition, Fouda (2009) examined the most suitable conditions for separating brown rice and paddy rice using a screen-type paddy rice separator (model: SATAKE Ps 120E). It was found that the optimal inclination angle of the sieve for minimizing the cracking of the rice was 15° at a speed of 200 rpm, with seed moisture of 14 % on a wet basis (w.b.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical analyses by Fouda (2009) revealed that the optimum sieve speed of 0.5 m/s (200 rpm) is recommended to prevent riding of material on the sieve surface. The experimental results reveal that the cleaner performance was in the optimum region under sieve angle of 15° and paddy moisture content of 14 %.…”
Section: Introductionmentioning
confidence: 99%